นมแพะ : ทางเลือกใหม่เพื่อสุขภาพ - นามโฮง ทศพร (RMUTSB ACADEMIC JOURNAL, 2013)
นมแพะแหล่งสารอาหารที่สำคัญชนิดหนึ่งจากสัตว์เลี้ยงลูกด้วยนม ปริมาณการผลิตนมแพะเพิ่มขึ้นถึงร้อยละ 30 ภายใน 10 ปี คุณค่าทางโภชนาการและสารอาหารในนมแพะเหมาะที่จะเป็นทางเลือกหนึ่งเพื่อสุขภาพสำหรับผู้บริโภค เมื่อเปรียบเทียบ กับนมวัว นมแพะมีสัดส่วนของปริมาณของแข็งทั้งหมดสูงกว่านมวัว ในส่วนขององค์ประกอบโปรตีนมีกรดอะมิโนจำเป็นมากกว่า และกรดอะมิโนอิสระทอรีนที่มีประโยชน์ต่อสุขภาพสูงกว่าถึง 20 เท่า ไขมันในนมแพะมีอัตราส่วนของกรดไขมันชนิดโอเมก้า 6 ต่อ โอเมก้า 3 ที่ต่ำซึ่งดีต่อสุขภาพ เม็ดไขมันมีขนาดเล็กกว่า 5 ไมครอน มีอยู่ถึงร้อยละ 80 ทำให้มีเนื้อสัมผัสที่นุ่ม นมแพะมีแร่ธาตุ และวิตามินสูงแต่ขาดกรดโฟลิกและวิตามินบี 12 ซึ่งสามารถเสริมได้จากอาหารชนิดอื่น อย่างไรก็ตามคุณสมบัติต่างๆของ นมแพะก็เป็นทางเลือกหนึ่งที่ช่วยแก้ปัญหาให้กับผู้บริโภคที่แพ้นมวัวหรือผู้ที่มีปัญหาเกี่ยวกับระบบย่อยอาหาร และปัญหาด้าน สุขภาพอื่นๆ Goat milk : Alternative for human health benefit Goat milk, one of the important sources of nutrient from mammal, is 30% increasingly produced in 10 years. Goat milk is high in nutritional value and nutrients, which could be another alternative for human health promoting. Compared to cow milk, goat milk posses more total solid and essential amino acid contents. The content of taurine, the health beneficial free amino acid, is 20 times more than that in cow milk . The ratio of omega 6 to omega 3 is low which identified to be the good quality fat. Due to 80 percent of the small size of fat globules (< 5 μm) in goat milk fat, the texture is soft. Goat milk contains high amount of minerals and vitamins except folic acid and vitamin B12 which are deficient , but it could be supplemented from other sources of food. However, because of its nutritional utilization, it can be one of the alternatives for the consumers who are allergic to cow milk, who have digestive problems and who are concerned about their health.